Strategy of the Democratic Party in the Legislative Election in Malacca Regency in 2019 - Piere Mario Bait; Randy Vallentino Neonbeni (IHSA Institute, 2022)
The author is interested in conducting this research related to the Strategy of the Democratic Party in the Legislative Election in Malacca Regency in 2019. The type of research used is juridical-empirical research. The source of this research data is primary data, primary data is direct data that comes from Law Number 17 of 2017 concerning General Elections and interviews conducted in the field. In this study, primary data were obtained directly from the field, in the form of notes on observations and interviews with research subjects; and Secondary Data, Secondary data is supporting data for primary data. In writing, the researcher gets secondary data from books, journals, and other supporting sources related to the author's research so that it can be used as a reference in the preparation of the research. The results show that the strategies used by the Democrats are offensive strategies, defensive strategies, imaging strategies and character strategies. . Where the offensive strategy uses a market expansion strategy to form a new group of voters by lighting up the political base of the opponent's mass base. Ability to create new innovations in conducting campaigns. Offensive strategy played by the entire team which includes the Democratic Party Team, Volunteer Team and other small teams. Meanwhile, the defensive strategy used is the Democratic Party's approach to it intensively and continuously without getting tired. This approach is useful for introducing the Party and its programs and also introducing prospective legislative candidates. Imaging Strategy, the Democratic Party also uses communication, namely socialization, meeting directly with the community and conducting campaigns through electronic media, newspapers and radio. Character strategy, the figure of Susilo Bambang Yudhoyono (SBY) as a builder of the Democratic party, his expertise in building an image (as a polite, honest and benevolent leader), who loves the community. The Democratic Party first conducts a survey and selection of the figures who will enter the fight in the legislative election. The Democratic Party in carrying out an offensive strategy in coordinating between teams well. The Democratic Party needs to develop new programs that allow the people to be attracted again, and make the people prosperous by optimizing the socialization of the new program. The Democratic Party needs to design a schedule or work agenda that based on the whole community, location and time consistently run well